Diagnóstico e ações de melhorias logísticas em um banco de alimentos: estudo de caso - Wirtzbiki, Bianca Telles (2013)
This dissertation is based on a case study conducted in a food bank located in Fortaleza/Brazil, named Mesa Brasil SESC. The objective of the research is to propose improvements to the logistics of the food bank in order to increase the level of service to registered associations. The logistics of Mesa Brasil is characterized by redistribution to the charities of food donated by partner companies. These foods are outside the standards of marketing, but still good enough for human consumption. The main sources of evidence used in the research were documents, files, semi-structured interviews, questionnaires, direct and participative observation. The following improvements were proposed for the problems identified in the Food Bank: a new route system was developed, allowing Mesa Brazil for the transportation of donations to the charitable associations; equipment acquisition of mobile compartments for the trucks of Mesa Brasil to separate incompatible cargoes during transportation; instruments for temperature monitoring in food storage; practice FIFO (first one in, first out); acquisition of shelves to organize donations according to perishability level and type of food; developing a strategy to capture donors; realization of monitoring visits associations in order to check the handling and use of donated food; integration meetings with employees; training of employees before beginning their activities; visits to suppliers ; reset the time windows for each donor; new layout proposed for the food bank.